Uniform excitations in magnetic nanoparticles - Mørup, Steen; Frandsen, Cathrine; Hansen, Mikkel Fougt (Beilstein Journal of Nanotechnology, 2010)
We present a short review of the magnetic excitations in nanoparticles below the superparamagnetic blocking temperature. In this temperature regime, the magnetic dynamics in nanoparticles is dominated by uniform excitations, and this leads to a linear temperature dependence of the magnetization and the magnetic hyperfine field, in contrast to the Bloch T3/2 law in bulk materials. The temperature dependence of the average magnetization is conveniently studied by Mössbauer spectroscopy. The energy of the uniform excitations of magnetic nanoparticles can be studied by inelastic neutron scattering.
Keywords: collective magnetic excitations; Mössbauer spectroscopy; neutron scattering; spin waves; superparamagnetic relaxation